Qualidade tecnológica do óleo de soja obtido de grãos armazenados em condições ambientais controladas - Bischoff, Tábata Zingano (2015)
Soy is an important Fabaceae, both for its high nutritional value, as for the commercial production of oil, which is mainly used in human food. The reaction oxidation that takes place in oils and fats is one of the main causes of the deterioration of food, causing thus a decrease of the nutritional quality and the quality of crude oil, which can be remedied or even prevented through the storage appropriate the grain, temperature, relative humidity and the dried optimum of the grain. Given the above, the objective of this study was to evaluate the main changes in the quality the soybean oil crude, present in grain the soybeans, from the storage of grain in the temperature of 30 °C and different relative humidity s (59,6, 67 and 76%). For this purpose, used grain on variety SYN 1059 RR, derived from a grain processing company and producer of seeds of western Paraná. Soybeans grain It was packaged in plastic recipients, within were placed in saturated salt solutions so that the grains reach the desired moisture. The analyzes the dried, lipid, acid value, color, antioxidant capacity, specific extension by absorption in the ultraviolet region were made during storage, because the correlation between these properties indicates the degree of oil oxidation and, consequently, the quality of the grain. A completely randomized design, in a split plot and the results were submitted to analysis of variance and mean comparison test. The storage time caused changes in physical-chemical properties of the grains, therefore, the oil was degraded over time. Another factor that influenced the degradation was the relative humidity because, with the smallest lower relative humidity (56,9%) and most (76,0%) showed the largest degradation.